Transculturation in The gift of rain and The calligrapher's daughter - Ng, Wen Lee (2015)
This study undertakes the reading of complex interactions between various cultures portrayed in two novels, Tan Twan Eng’s The Gift of Rain (2009) and Eugenia Kim’s The Calligrapher’s Daughter (2010). While the growing body of research on The Gift of Rain focuses on the protagonist, Philip Hutton’s traumatic condition, his Chinese identity, and his ambiguous identity, this study devotes particular attention to the complexity of interactions between various cultures practised by Philip. On the other hand, although reviews on The Calligrapher’s Daughter have highlighted the protagonist, Han Najin’s namelessness state, collision of cultures between tradition and modernity, and her conflicting emotions towards Christianity, the complex interactions between various cultures practised by Najin appear to have been neglected. This study then aims to address these gaps by applying the concept of transculturalism to analyse the processes of acquiring foreign cultures and incorporating the foreign cultures intotraditional cultures experienced by Philip and Najin. In other words, this study employs the concept of transculturalism, which stresses the transitional process from one culture to another, to examine multicultural depictions in the selected novels. Scholars, such as Khan, Tiwari, Sheoran and C. S. Tan who have examined multicultural depictions in various literary texts, have found that migration or colonisation leads to multicultural circumstances, which in turn cause certain ethnic groups to lose their cultures and identities; in other words, experience identity crisis or search for self-identity. Hence, the multicultural circumstances depicted are perceived as negative phenomena. However, this study has found that by examining the interactions between various cultures, rather than focusing on the end products such as portrayals of hybridity, the positive sides of multicultural depictions could be revealed. In the first stage of transculturation process, the acculturation stage, both protagonists, Philip and Najin,acquire foreign cultures due to cultural marginalisation. In the second stage, the deculturation stage, Philip and Najin lose as well as rediscover their traditional cultures. Then in the final stage, the neoculturation stage, they struggle to incorporate the foreign cultures they have acquired into their traditional cultures in order to form new cultural practices. These three stages in the transculturation process experienced by Philip and Najin show that the new cultural practices they have created are made up of both their traditional cultures and the foreign cultures they have acquired. This means that Philip and Najin do not totally lose their traditional cultures and identities. Therefore, this study concludes that multicultural depictions in the two selected novels could be read positively, provided that the interactions between various cultures, which resulted in the incorporation of foreign cultures into traditional cultures, are examined.